SYSTEMATIC LITERATURE REVIEW (SLR) : THE EFFECT OF CLAIMS EXPENSE AND UNDERWRITING ON INSURANCE COMPANY PROFITS - Veronica, Deka; Dani, Rian; Irmanelly, Irmanelly; Asrini, Asrini (Journal of Business Studies and Management Review, 2024)
This study aims to map the effect of claim and underwriting expenses on insurance company profits. In a study using the Systematic Literature Review method, 16 articles out of 200 articles were found that fit the criteria, with search strings from 2018 to 2022. The results showed that (RQ1) the problems contained in various research journals, namely differences in results from previous studies on the cost of claims and underwriting on profits and the decline in insurance company profits. In research conducted by Puja Yana, Melvi Muchlian, Sari Arsita (2022), the amount of profit obtained is a sensitive matter for stakeholders. In research conducted by Dwi Ayu Fitrianty, et al (2022), the gaps that occurred in previous research, it was concluded that not all empirical events were in accordance with theory. Research question results (RQ2) The research method that is often used is quantitative methods, this method is very relevant because quantitative research views the "Facts / Truths" that are in the object of research out there, and researchers must be neutral whatever is found in the field and impartial. Furthermore, the results of the research question (RQ3) Every year there are journals that discuss the effect of claims and underwriting expenses on insurance company profits, even in 2022 most journals use quantitative methods with different publications.